Associations Between Childhood Trauma and the Age of First-Time Drug Use in Methamphetamine-Dependent Patients - Huang, Cui; Yuan, Qiuyu; Zhang, Ling; Wang, Lei; Cui, Shu; Zhang, Kai; Zhou, Xiaoqin (Frontiers in Psychiatry, 2021)
Childhood trauma is related to substance use disorder; however, few studies have examined the relationship between childhood trauma and the age at which the drug was first used. The aim of this study was to investigate the relationship between childhood trauma and the age of first-time drug use among methamphetamine-dependent patients. Moreover, we analyzed the characteristics of adverse family environment associated with severe childhood trauma and the risk factors for starting drugs in minors. A baseline interview was conducted with 110 participants who were in detoxification, including demographic information, past substance use, and age of first-time drug use. The participants’ childhood trauma experience before 18 years of age was evaluated using the simplified version of the Childhood Trauma Questionnaire (CTQ-SF). The Chinese version of the Family Environment Scale (FES-CV) was used to assess the family environment of methamphetamine-dependent patients. Among 110 non-injecting methamphetamine-dependent patients, nearly half (n=48, 43.6%) had moderate and severe childhood trauma. Correlation analysis showed that the age of first-time drug use negatively correlated with emotional abuse (r=-0.32, p<0.01) and physical abuse (r=-0.27, p<0.01). The age of first-time drug use negatively correlated with conflict (r=-0.20, p<0.05) and independence (r=-0.22, p<0.05) of family environment, but positively correlated with intellectual-cultural orientation (r=0.28, p<0.01). Additionally, childhood trauma factors significantly correlated with many indexes of family environment, especially cohesion (r=-0.45, p<0.01), conflict (r=0.49, p<0.01), and independence (r=0.33, p<0.01). Additionally, the regression model showed that when emotional abuse increased by 1 point, the age of first-time drug use was 0.69 years earlier. These findings suggest that a detrimental family environment can aggravate childhood trauma, and the experience of childhood emotional or physical abuse may be an effective predictor of early drug use among methamphetamine-dependent patients.